Barriers to the adoption of the circular economy in the Brazilian sugarcane ethanol sector - Jesus, Gessica Mina Kim [UNESP]; Jugend, Daniel [UNESP]; Paes, Luis Alberto Bertolucci [UNESP]; Siqueira, Regiane Máximo [UNESP]; Leandrin, Matheus Artioli [UNESP] (Springer Nature, 2021)
Abstract: Brazil plays a prominent role in the global production of sugarcane and contributes to the renewable energy sector by producing ethanol. However, few studies have explored the adoption of the circular economy in the sugarcane ethanol sector. This article is aimed at analyzing and prioritizing barriers to the adoption of the circular economy in leading Brazilian sugarcane ethanol companies. For this, the analytical hierarchy process method and case studies methods were used. The main barriers identified were economic and financial, mainly due to dependence on high investments in production process technologies and the resulting uncertainties about returns. Another barrier was the lack of Brazilian legislation concerning the circular economy. We discuss the implications of our findings and present mechanisms for overcoming barriers and the role in supporting circular economy adoption in emerging economies. Graphic abstract: [Figure not available: see fulltext.]
Keywords: Bioeconomy; Bioethanol; Developing countries; Multi-criteria decision analysis; Sustainable design